Radiation protection issues in the excavation of road and railway tunnels, a preliminary assessment. Issue 9 (1st September 2016) - Cucchi, G.; Lisardi, A.; Mostacci, D.; Tositti, L.; Tugnoli, F.; Vichi, S.
ABSTRACT: In road and railway tunnel excavation, personnel are exposed to natural radiation. Exposure can have varying degrees of significance, as naturally occurring radioactive material (NORM) content may vary by more than one order of magnitude depending on local lithology and, as far as radon is concerned, depending also on features of more distant bedrocks involved in radon convection. Radon exhalation and build up in the confined environment of the tunnel is affected by permeability of rocks, which is highly variable with lithology. Excavation methods as well have an impact on workers' exposure, due both to exposure time and to protection afforded by the equipment. Therefore, it is of interest to develop a method to predict radon levels to characterize the work area. Since drill cores are invariably taken before excavation begins, for a preliminary assessment of the geology involved, a method is proposed here for predicting radon levels, based on NORM and exhalation measurements in drill core samples, and on the geometry of the tunnel to be excavated. An experimental campaign is under way on a railway tunnel under construction in northwestern Italy: preliminary results will be presented and predicted values compared to experimental measurements.